I am trying to find a solution to the following system where f and g are R^2 -> R^2 functions:
f(x1,x2) = (y1,y2)
g(y1,y2) = (x1,x2)
I tried solving it using scipy.optimize.fsolve as follows:
def eqm(vars):
x1,x2,y1,y2 = vars
eq1 = f([x1, x2])[0] - y1
eq2 = f([x1, x2])[1] - y2
eq3 = g([y1, y2])[0] - x1
eq4 = g([y1, y2])[1] - x2
return [eq1, eq2, eq3, eq4]
fsolve(eqm, x0 = [1,0.5,1,0.5])
Although it is returning an output, it does not seem to be a correct one as it does not seem to satisfy the two conditions, and seems to vary a lot with the x0 specified. Also getting a warning: 'The iteration is not making good progress, as measured by the improvement from the last ten iterations.' I do know for a fact that a unique solution exists, which I have obtained algebraically.
Not sure what is going on and if there is a simpler way of solving it, especially using just two equations instead of splitting up into 4. Something like:
def equations(vars):
X,Y = vars
eq1 = f(X)-Y
eq2 = g(Y)-X
return [eq1, eq2]
fsolve(equations, x0 =[[1,0.5],[1,0.5]])
Suggestions on other modules e.g. sympy are also welcome!
CodePudding user response:
First, I recommend working with numpy arrays since manipulating these is simpler than lists.
I've slighlty rewritten your code:
import scipy.optimize as opt
def f(x):
return x
def g(x):
return x
def func(vars):
input = np.array(vars)
eq1 = f(input[:2]) - input[2:]
eq2 = g(input[2:]) - input[:2]
return np.concatenate([eq1, eq2])
root = opt.fsolve(func, [1, 1, 0., 1.2])
print(root)
print(func(root)) # should be close to zeros
What you have should work correctly, so I believe there is something wrong with the equations you're using. If you provide those, I can try to see what may be wrong.
CodePudding user response:
This seems to be more of a problem of numerical mathematics than Python coding. Your functions may have "ugly" behavior around the solution, may be strongly non-linear or contain singularities. We cannot help further without seeing the functions. One thing you might try is to instead solve a system
g(f(x)) - x = 0
and simplify g(f(x)) as much as possible analytically. Then calculate y = f(x) after solving the equation.